Search for Novel Antagonist/S of HIF-1α from Selected Synthetic Analgesics/ Bioactive Flavonoids: An In-Silico Approach: Pharmaceutical Science-Drug Design and Development - Saha, Moumita; Rahman, Rumana; Mukherjee, Anisha; Ghosh, Chandreyi; Chatterjee, Sirshendu (International Journal of Life Science and Pharma Research, 2023)
Computer aided drug designing as well as drug repurposing implies the usage of molecular modelling techniques like analysis of the structures of receptor and ligand, molecular docking, pharmacokinetics and toxicity prediction, to explain the bioactivity of the synthetic molecules or plant secondary metabolites to design more efficient drug candidates or to repurpose an old drug in new diseases. Numerous studies have demonstrated that the low oxygen environment inside the cell is a key factor in developing breast cancer metastasis. To gain insight into the spread of breast cancer, hypoxia-inducible factor 1 (HIF-1), one of the master regulators of the hypoxic response, has been intensively explored. Our current research focuses on the insilico analysis and comparative study to evaluate the effects of different cancer drugs, analgesics, and plant-derived flavonoid compounds on HIF-1α regulation of breast cancer metastasis. According to the study, Quercetin shows the maximum binding affinity, i.e., -8.2 kcal/ mol. followed by Letrozole (-7.3 kcal/mol.), Naringenin (-7.11 kcal/mol), Tamoxifen (-7.07 kcal/mol), Phenacetin (-6.16 kcal/mol), and Aspirin (-5.7 kcal/mol). The study highlighted that Quercetin has the strongest binding affinity whereas Aspirin has the least binding affinity with HIF-1α protein. Hence the least toxic compound Quercetin can be a good candidate to control breast cancer metastasis by modulating the HIF-1 pathway.